2018
DOI: 10.3390/molecules23071588
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structures and Biological Activities of Limonoids from the Genus Swietenia (Meliaceae)

Abstract: Swietenia is a genus in the plant family Meliaceae. This genus contains seven to eight known species, found in the tropical and subtropical regions of the Americas and West Africa. Thus far, more than 160 limonoids have been isolated from four species of the genus Swietenia. Limonoids are rich in structure type and biological activity, and these compounds are the main active components in the Swietenia species. This paper will give a comprehensive overview of the recent phytochemical and pharmacological resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Until now, they are reported to distribute mainly in Rutaceae and Meliaceae plant resources. Previous studies suggested that limonoids exhibited strong anti-inflammatory activity (Akihisa et al, 2017;Hu et al, 2018;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, they are reported to distribute mainly in Rutaceae and Meliaceae plant resources. Previous studies suggested that limonoids exhibited strong anti-inflammatory activity (Akihisa et al, 2017;Hu et al, 2018;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies have revealed a great variety of pharmacological activities [ 22 , 23 , 24 ] as well as health-promoting and disease-preventing properties exhibited by limonoids [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…e Meliaceous plant S. macrophylla grows widely in Central and South American countries, India, Malaysia, and China [1,4]. It is rare to see in Vietnam, and the phytochemical investigation, as well as antifungal properties of the local species, has not been reported much.…”
Section: Discussionmentioning
confidence: 99%
“…From the fruits of K. senegalensis, Abdelgaleil et al (2004) also successfully isolated bioactive limonoids such as seneganolide A, 2-acetoxyseneganolide A, and methyl 6-hydroxyangolensate with antifungal effects on B. cinerea [9]. In our ongoing research studies on bioactive limonoids from Meliaceous plants growing in Vietnam, we successfully isolated and identified nine limonoids from Melia dubia (1-2), Aphanamixis polystachya (3)(4)(5), and Swietenia macrophylla (6)(7)(8)(9). e antifungal potential of the isolated limonoids against various phytopathogenic fungi including F. oxysporum, M. oryzae, S. rolfsii, R. solani, Alternaria spp., B. cinerea, and oomycetes Phytophthora species was evaluated in vitro.…”
Section: Introductionmentioning
confidence: 99%